2018
DOI: 10.1515/zpch-2017-1048
|View full text |Cite
|
Sign up to set email alerts
|

Protease-mediated Inflammation: An In Vitro Human Keratinocyte-based Screening Tool for Anti-inflammatory Drug Nanocarrier Systems

Abstract: Background: Refined encapsulation approaches in dermatotherapy gain increased interest. There is need of reproducible in vitro systems representing disease features to screen drug delivery systems for preclinical assessment. Inflammatory human skin diseases are commonly accompanied by abnormal epidermal differentiation and barrier impairment. Serine proteases (SPs) and their inhibitors play a critical role in such dysfunctional differentiation. SPs also initiate cellular pathways via activation of protease-act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…In previous investigations, however, Li et al elegantly demonstrated the role of plasmin as an amplifier of skin inflammation using intradermal injections of phosphate-buffered saline compared to plasmin in murine skin [41]. The overall observation of the combined SP treatment being a moderate inflammatory stimulus is in accordance with our own experiments using human keratinocyte cultures, which showed that the addition of low concentrations of trypsin and plasmin resulted in a mild-to-moderate radical formation, as assessed by electron paramagnetic resonance (EPR), while also increasing IL-6 and IL-8 levels without impairing the overall cell viability [54]. In vivo, increased TEWL values, as observed in the culture model, were positively correlated with an enhanced activity of plasmin and trypsin-like KLKs in the stratum corneum.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In previous investigations, however, Li et al elegantly demonstrated the role of plasmin as an amplifier of skin inflammation using intradermal injections of phosphate-buffered saline compared to plasmin in murine skin [41]. The overall observation of the combined SP treatment being a moderate inflammatory stimulus is in accordance with our own experiments using human keratinocyte cultures, which showed that the addition of low concentrations of trypsin and plasmin resulted in a mild-to-moderate radical formation, as assessed by electron paramagnetic resonance (EPR), while also increasing IL-6 and IL-8 levels without impairing the overall cell viability [54]. In vivo, increased TEWL values, as observed in the culture model, were positively correlated with an enhanced activity of plasmin and trypsin-like KLKs in the stratum corneum.…”
Section: Discussionsupporting
confidence: 87%
“…It was adapted from experimental protocols to make use of its proinflammatory properties. In cell cultures studies with keratinocytes exposed to 2.3 µg/mL trypsin, we identified this concentration as a moderate stimulus for the induction of the free radicals IL-6 and IL-8 [ 54 , 55 ].…”
Section: Methodsmentioning
confidence: 99%
“…Similar to previous work, this pretreatment was performed to model the enzymatic activity, cytokine environment, and barrier alteration typical of inflamed skin. 38 , 39 The samples were treated with a cotton swab for removing the formulation still sticking to the skin surface and subsequently prepared for STXM studies by fixation in 2.5% glutaraldehyde and 1% cacodylate buffer. Finally, they were embedded in EPON resin (Serva, Heidelberg, Germany) and cut into 200–300 nm slices with an area of typically 500 μm × 500 μm using an ultramicrotome, similar to previous work.…”
Section: Methodsmentioning
confidence: 99%
“…Trypsin applied in moderate concentrations capable of triggering inflammatory processes has been used as a stimulus in cell cultures to mimic enhanced serine protease activity, typically found in inflammatory skin diseases, such as atopic dermatitis. 38 , 39 It is also known that trypsin-like serine proteases in the SC are associated with desquamation. 40 These proteases are found to be more active in the outer SC than in the inner part of this skin layer.…”
Section: Introductionmentioning
confidence: 99%
“…The skin surface was pre-treated with serine protease (SP) to induce an impairment of the SC barrier, 32 , 33 activation of PAR2-mediated inflammatory cytokine release, 34–37 and free radical formation. 38 Furthermore, Jurkat cells were added to the system and activated with phytohaemagglutinin (PHA) and Th17 cytokines (IL-17A and IL-22) to reproduce the inflammatory environment typical for psoriasis. 39 This skin-cell co-culture set-up allowed us to measure the selectivity of drug release by oxidative-sensitive CMS nanocarriers as well as the effects of the delivered drug towards inflammatory T cells.…”
Section: Introductionmentioning
confidence: 99%